THE ROLE OF GENETIC TESTING IN EARLY DETECTION OF ONCOLOGICAL DISEASES - Sheraliyev Ilyosjon Ibroxim oʻgʻli (Sciental Journals Publishing, 2025)
This article examines the role of genetic testing in the early detection of oncological diseases. Genetic diagnostic tools, particularly molecular analyses, are evaluated as important instruments for identifying individual characteristics of cancer, assessing risk factors, and developing personalized prevention and treatment strategies. The article analyzes the effectiveness and prospects of genetic testing based on contemporary scientific research.
Keywords: Genetic testing, oncological diseases, early diagnosis, BRCA1, molecular diagnostics, PCR, personalized medicine.